Mortality Responses of Spodoptera litura Following Feeding on BT- Sprayed Plants - Saad A. AlOtaibi, (Journal of Basic & Applied Sciences, 2013)
Bacillus thuringiensis delta-endotoxins are safe biological insecticidal proteins whose usefulness has long been recognized. The first commercialized Bt insecticidal formulations were composed of spore-crystal preparations derived from wild-type strains. These products generally have a limited insecticidal host range and several genetically modified strains have, therefore, been constructed in this study using conjugation procedure. However, addition of a new plasmids to Bt strains already harboring other genes often resulted in broader - spectrum. Bacillus thuringiensis serovar Kurstaki, Bacillus subtilis and four of their transconjugants were used in this study as a biocontral agents against lepidopterous cotton pest. Bacterial transconjugants were evaluated for their hybrid vigor in relation to the mid parents and better parent. This evaluation was related to survival and mortality percentages induced in Spodoptera littoralis larvae. Two groups of bioinsecticides; crystals, crystals + endospores were used to be evaluated in this study. The results appeared that bioinsecticides containing crystals + endospores was more effective than crystals for increasing mortality percentage and reducing survival percentage. This effective was including reduction in the mean number of Spodoptera littoralis larvae feeding on leaves sprayed with crystals + endospores. Increasing mortality percentage of crystals + endospores was due to higher toxicological effects than that of crystals. This recommended bioinsecticide biologists to use crystals + endospores in all bioinsecticides formulations. Higher positive efficiency was appeared at 168 h of treatments. Recombinant Bacillus thuringiensis was more effective as biocontrol agents against lepidopteran pests at the early instars, because susceptibility was decreased with larval development. This indicated that the first instars were more susceptible to Bt sprayed plants than the later instar stages. The combined effects of crystals + endospores produced higher mortality. This factor was important to be considered in designing resistance management strategies.